PENGARUH PENGGUNAAN BAGIAN-BAGIAN KARKAS SAPI TERHADAP KUALITAS BAKSO - Manek, Jefrianus S (Jurnal Sains Peternakan, 2014)
The aim of this research was to analyse of the parts beef carcass on the pH and sensoryproperties of meatball. This research was conducted on January 1st unti February 1st 2013 in animal husbandry faculty of  Kanjuruhan University laboratory. The method used is the experiments with Completely Randomized Design ( CRD ) with three treatment of the parts beef carcass, that is the Chuck ( P ) Shank ( S ),  and the mixture of chunk and shank. The result showed that parts of the beef carcass were no significant affected ( P > 0.05 ) on pH. The result of  this research showing that  pH prouction are the same that is 5.5 at all treatment, while normal pH at fresh beef is 7.0. No significant diffrence  ( P > 0.05 ) were observed among visual flavour and aroma. But significant affected ( P< 0.01 ) to colour and texture on sensory analysis.Keywords: : Meatball, Meat, and Parts of Beef Carcass